Mineral water of the Yakovlev deposit of high-grade iron ores (KMA): diagnostics and usability - R. E. Dashko (Известия высших учебных заведений: Геология и разведка)
Perennial complex monitoring carried out in the underground workings has revealed three types of mineral water: I (YM) - sodium chloride groundwater from the ore bodies with mineralization 2,6-3,0 g/dm3; II (YM) - sodium chloride water from granite massif with a high concentration of bromine and boron and mineralization 11-13 g/dm3; III (YM) - chloride sodium water that comes from a high head aquifer overlying the ore formation, has mineralization 0,7-1,6 g/dm3 and a high content of fluorine up to 12-14 g/dm3. Sanitary-hygienic and radiological indicators of this water are in compliance with the current standards. The methods of capping of all three groundwater types have been developed providing the absence of contamination and an automatic time control of main balneological components level. Mineral water bottling line is designed.